Implementasi Senam Yoga Dalam Mengurangi Sesak Nafas Pada Pasien PPOK - Zuriati Zuriati; Melti Suriya (Jurnal Pengabdian Harapan Ibu (JPHI), 2020)
One of the effects of Chronic Obstructive Respiratory Disease (COPD) is respiratory problems with progressive symptoms of shortness of breath. The impact of prolonged shortness of breath can cause sufferers to be restless and unable to sleep so that sleep patterns are disturbed. The purpose of providing community service, especially COPD patients, is to help reduce the perceived shortness of breath so that the patient's sleep quality is resolved. The method that will be given to this community is to practice yoga 30 minutes twice a week. The number of patients who do this yoga exercise is 6 people who suffer from COPD. The community service results obtained that COPD sufferers can do yoga exercises gradually. Yoga Gymnastics is a physical activity that helps to breath. So it is hoped that in COPD patients with this breathing exercise can help patients reduce the perceived tightness so that the quality of sleep can be fulfilled. This The community service can be carried out by nurses in overcoming congestion of patients both in the community and in clinical practice. Kata Kunci : COPD , Sleep Quality, Yoga Training